Understand acceptance and opposition to geothermal energy in Iceland - Julia Lee Reimer 1999- (2023)
Transitioning from fossil fuels to renewable sources of energy is a crucial component to mitigating current effects and preventing further consequences of human-induced climate change. One such renewable energy source is geothermal energy, a viable source of energy in Iceland as well as other parts of the world. Energy projects, however, often face public opposition even if they are renewable, particularly from the communities in which they are being developed. This research investigates the successful development of geothermal energy in Iceland through a literature review of energy development in the country, a survey gauging public knowledge and perception of geothermal energy, and several interviews with identified stakeholders of the Hellisheiði Power Station. Quantitative survey results showed relatively high knowledge and acceptance of geothermal energy in the public compared to previous research on geothermal acceptance in Germany. A thematic analysis of the open-ended survey questions and stakeholder interviews produced four main topics relating to acceptance and support of geothermal projects: Usage, Economics and Public Policy, Environmental Impact, and Longevity. Geothermal projects can foster public acceptance by successfully addressing and integrating these themes in their early planning and operations. Furthermore, these themes are not specific to geothermal energy nor Iceland and can be applied to other renewable energy projects around the world. Vegferðin við að innleiða endurnýjanlega orkugjafa í stað jarðefnaeldsneytis er mikilvægur þáttur til að mæta núverandi áhrifum og forðast enn meiri afleiðinga af mannlegum þáttum sem tengjast loftlagsbreytingum. Einn slíkra orkugjafa er jarðvarmi, sem er einmitt mikilvægur orkugjafi fyrir Ísland sem og aðrar þjóðir í heiminum. Hins vegar verða orkuverkefni oft fyrir andstæðu almennings jafnvel þótt þau séu endurnýjanleg orkuverkefni, sérstaklega í samfélögum þar sem þau hafa verið tilstaðar sem lengst. Þetta verkefni rannsakar velheppnaða þróun á ...